Religious and quasi-religious attitudes in four Polish documentaries from 2008–2019 - Kopczyński, Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The paper aims to present different ways of showing religious and quasi-religious attitudes in contemporary Polish documentaries. The discussion is based on four feature-length films: Kites by Beata Dzianowicz (2008), Communion by Anna Zamecka (2016), Who Will Write Our History by Roberta Grossman (2018), and Tell No One by Tomasz Sekielski (2019). The author evaluates the methodological usefulness of reflection in the documentary of the “religious film” category used in Polish research and the concept of “transcendent(al) style” taken from Paul Schrader’s book. Occasionally touching upon the question of the relationship with audiences, the author also mentions the paradigm of Polish Romanticism present in contemporary culture.